The Role of Lactobacillus reuteri DSM 17938 in Athletic Performance and Recovery - Julia Charkot; Wojciech Bieńkowski; Irmina Jaszczuk (Quality in Sport, 2025)
Introduction and purpose: The gut microbiota plays a vital role in modulating health, immunity, and recovery, all of which are crucial for athletes. Limosilactobacillus reuteri DSM 17938 is a well-documented probiotic strain with anti-inflammatory, immunomodulatory, and gastrointestinal benefits. This review explores its potential application in supporting athletic performance and post-exercise recovery.